2011
DOI: 10.21608/jfds.2011.81841
|View full text |Cite
|
Sign up to set email alerts
|

QUALITY OF RAS CHEESE MADE BY PROBIOTIC STRAIN OF Lactobacillus rhamnosus

Abstract: Five Ras cheese treatments were made by replacing normal cheese starter with Lactobacillus rhamnosus. Cheese treatments were microbiologically, chemically and organoleptically evaluated when fresh and after 1,2,3 and 4 months. Moisture content decreased, while total nitrogen, fat, ash, titratable acidity, soluble nitrogen, total volatile fatty acids (TVFA), Shilovich number and score of organoleptic properties increased by replacing the normal cheese starter with Lactobacillus rhamnosus, and the increases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 9 publications
20
12
1
Order By: Relevance
“…The TS content of white soft cheese increased as the pickling period advanced and by increasing the L. rhamnosus level due to the decrease in the moisture content in cheese and increasing the bacterial counts. These results are in an agreement with these reported by Badawi and Kebary (1996) and Kebary et al (2015). Moreover, the control samples (C) had lowers TS than that of white soft cheese made with different levels of L. rhamnosus.…”
Section: Total Solid Contents (Ts)supporting
confidence: 93%
See 1 more Smart Citation
“…The TS content of white soft cheese increased as the pickling period advanced and by increasing the L. rhamnosus level due to the decrease in the moisture content in cheese and increasing the bacterial counts. These results are in an agreement with these reported by Badawi and Kebary (1996) and Kebary et al (2015). Moreover, the control samples (C) had lowers TS than that of white soft cheese made with different levels of L. rhamnosus.…”
Section: Total Solid Contents (Ts)supporting
confidence: 93%
“…Adding L. rhamnosus up to 0.75% improved the organoleptic properties of the resultant cheese. Fat, TN, salt, ash, SN content, TVFFA, shilovich number and scores of organoleptic properties increased as pickling period proceeded, while moisture content and TN content decreased (Kebary, 2015). Egyptian consumers are cheese consumer more than fermented milk products (Motawee, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…The data show a slight gradual increase in cheese fat content during the storage period which may be attributed to the gradual decrease in cheese moisture during storage. Our results are in agreement with that obtained by Genied (1990), Saleh (2003), El-Fadley (2010) and Kebary et al, (2011).…”
Section: Cheese Aciditysupporting
confidence: 94%
“…It was observed that (SRI) increased with the advancement of storage period from 41.6 ± 1.43 at the beginning to 80.5 ± 2.0 at the end of storage period (P < 0.05). Increasing ripening index with time is in agreement with the reports of Abdalla & Abdel Razig (1997), Abdel Razig (2000, Tarakci & Kucukoner (2006), and Kebary et al, (2011). The increase was mainly due to breakdown of proteins with the advancement of storage period (Abdu & Dawood, 1977, Saleem & Abdel Salam, 1979.…”
Section: Shilovich Ripening Index (Sri)supporting
confidence: 89%
“…The lowest numbers for Streptococci and Lactobacilli were in C 2 at 14 days of storage. Similar results were reported by Kebary et al (2015). The viable counts of Lactobacilli in all fresh UF-Kariesh cheeses were varied from 6.58 to 8.80 log cfu/g, whereas it reached to 8.…”
Section: Microbiological Examination Of Different Kariesh Cheese Treasupporting
confidence: 88%